Slavery and the death penalty: a study in abolition - Malkani, Bharat (Law, justice and power, 2018)
It has long been acknowledged that the death penalty in the United States of America has been shaped by the country’s history of slavery and racial violence, but this book considers the lesser-explored relationship between the two practices’ respective abolitionist movements. The book explains how the historical and conceptual links between slavery and capital punishment have both helped and hindered efforts to end capital punishment. The comparative study also sheds light on the nature of such efforts, and offers lessons for how death penalty abolitionism should proceed in future. Using the history of slavery and abolition, it is argued that anti-death penalty efforts should be premised on the ideologies of the radical slavery abolitionists